Development of High-Yielding and Stable Maize (Zea Mays L.) Hybrids Tolerant to Acid Soils of the Tropical Humid Forest Zones of Cameroon - Ngoune, T.L (University of Ghana, 2014)
Maize is the most important cereal produced in the Bimodal Humid Forest Zone (BHFZ) of Cameroon. Yield of the crop in the BHFZ is very low because of the negative impact of soil acidity especially Al toxicity on plant growth. Liming increases soil pH levels reduces the level of Al saturation and boost the productivity but it is costly and unavailable. Therefore, it becomes necessary to explore more sustainable and affordable ways of increasing yield of the crop. The objective of the present study was to identify high-yielding and stable maize hybrids tolerant to acid soils. A Participatory Rural Appraisal (PRA) was conducted in the BHFZ to identify farmer constraints to maize production and varietal preferences. Results indicated that farming is undertaken by the youth with maize being the most important cereal crop. Maize is grown for home consumption and for cash. Slash and burn associated with fallow systems were the predominant land management practices. The main constraints affecting maize production are low soil fertility, high cost of fertilizer, use of poor quality seeds, lack of improved varieties, and poor post-harvest handling and preservation methods. Farmers’ were willing to adopt new and improved maize varieties. Farmers’ preferred traits in improved maize varieties were high yield, good quality grain, soft and sweet taste, early maturity, pest and disease resistance. A genetic diversity study was conducted on thirty hybrid parental materials used to assess the variability among them using agronomic traits and molecular markers. These lines (13 from IRAD, 14 from CIMMYT and three from IITA) were evaluated in acid soil environments from 2013 to 2014. Fresh leaf samples of the 30 lines were collected at 14 days old and genotyped using 200 SNP markers. As results, the local inbred lines had flint and indented kernel, with a yellow color. Most of them had primary –secondary tassel type with reddish color. The inbred lines were grouped into two main clusters containing four groups with different levels of stress tolerance. Cluster I from the molecular characterization contained all the introduced inbred lines and most of the locally adapted lines subdivided into 16 sub-clusters. Cluster II had two Acid Tolerant Population (ATP) lines. There was low variability between Acid Tolerant Population (ATP) lines and introduced lines. The performance of 121 genotypes were subsequently evaluated in 12 environments made of acid soil and control soil conditions using a simple lattice design (11 x 11). Fifteen high-yielding hybrids were identified in these environments. All these hybrids out-yielded the best hybrid check variety by equal or more than 10%. Heritability estimates of all the traits recorded in acid soil environments was lower under acid than in control soil conditions. Yield reduction due to Al toxicity ranged from 2 to 69%. Then, the general and specific combining abilities of 112 hybrids and their parents were estimated using line by tester mating design. The results showed that Al tolerance for grain yield was under both additive and non-additive gene action with the non-additive gene action predominating. Four distinct heterotic groups were identified under acid soil and across environments. In control environments, two heterotic groups were identified. Cam Inb gp1 17 and 9450 were the best testers in control and across environments while 4001 was the best under acid soil environments. The yield stability study of 121 genotypes was carried out across nine environments using a lattice square design (11x11). The study environments were grouped into three mega-environments. Eight hybrids were the most high-yielding and stable hybrids across environments and could be potential hybrids for release after on-farm and multi-locational trials. Almost all these hybrids had at least one introduced parent suggesting that the introduction of inbred lines was effective to the development of high-yielding and stable maize hybrids under acid soil conditions.
Thesis (PhD) - University of Ghana, 2014